A retrospective study of attempted self-harm in a secondary care setting in rural India - Mysore, Seetharam; M., Vidyashree; Sajjalguddam, Shruti; Murthy, Deepak; N., Nagarathna; Martinez Rangel, Maria (International Journal Of Community Medicine And Public Health, 2023)
Background: Suicides and non-suicidal self-injuries (NSSI) pose a serious public health problem, affecting communities all over the world. Adolescents and young adults are particularly vulnerable to commit self-harm (SH). SH causes serious emotional, physical, and economic repercussions, and leads to long-term health impacts. Methods: A retrospective study was conducted in a rural secondary care hospital from Feb 2020 to March 2022. Data regarding demographics, cause and type of SH, and treatment provided to 190 patients were analysed. Results: Majority of patients were in the 16-35 years age group. Poison consumption was the commonest method used. Pesticides and pills were the commonly-used agents. Agricultural activities and pre-existing illness in families facilitated access to these agents, as did the unregulated availability and unsafe storage. 31 patients disclosed the reason for SH, with the commonest reason being strained relationships. Emotional states described by the patients which pushed them to SH included dejection, hopelessness, anger, recklessness, altered mood, lack of purpose in life, cynicism and a sense of lack of support. 16% were discharged against medical advice. Conclusions: The study identified the need for methodical documentation, referral and follow-up of patients, with adequate psychiatric and counselling support. Access to care for SH patients is lacking especially in rural areas, and is at best available only for management of the SH event. SH should be considered not as a disease by itself, but as an outcome of stress due to socio-economic and other factors. Multi-stakeholder convergent approaches are needed to tackle this challenge in a holistic manner.